Vegetative anatomy of Tabernaemontana alternifolia L. (Apocynaceae) endemic to southern Western Ghats, India - Seenu, Yuvarani; Ravichandran, Koshila Ravi; Sivadas, Anaswara; Mayakrishnan, Balachandar; Thangavelu, Muthukumar (Acta Biologica Szegediensis, 2020)
The anatomical description of vegetative parts of Taberenaemontana alternifolia L. belonging to the family Apocynaceae was investigated in the present study. The leaves of T. alternifolia is hypostomatic with paracytic stomata, uniseriate epidermis made up of thin-walled parenchymatous cells covered by thin cuticle on both adaxial and abaxial surfaces. The hypodermis comprises of angular collenchyma cells. Mesophyll is dorsiventral containing silica bodies and vascular bundles are bicollateral. The petiole is flattened adaxially and arch-shaped abaxially with a uniseriate epidermis covered by a thin cuticle. The hypodermis is 7-8 layered angular collenchyma cells consisting of laticifers and parenchymatic, cortical layers consisting of silica bodies and thick-walled fibers and U-shaped bicollateral vascular bundles. Secondary growth in stems is characterized by the formation of periderm and thick-walled fibers in the vascular tissues. Bicollateral vascular bundles are covered by sclerenchymatous patches, parenchymatous cortex and pith consist of fibers, laticifers and silica bodies. The root possess unicellular root hairs, compactly arranged thin-walled uniseriate epidermis, 16-18 layered cortex containing silica bodies and fibers, indistinct endodermis, radially arranged vascular bundles and 14-16 arched xylem. Pitted water-storage cells are present in the conjunctive tissue. Lignin deposition was observed in the root stelar region and pith is absent.